The Synthetic Antiviral Drug Arbidol Inhibits Globally Prevalent Pathogenic Viruses - Pécheur, Eve-Isabelle; Borisevich, Viktoriya; Halfmann, Peter; Morrey, John D.; Smee, Donald F.; Prichard, Mark; Mire, Chad E.; Kawaoka, Yoshihiro; Geisbert, Thomas W.; Polyak, Stephen J. (Journal of Virology, 2016)
Arbidol (ARB) is a synthetic antiviral originally developed to combat influenza viruses. ARB is currently used clinically in several countries but not in North America. We have previously shown that ARB inhibits in vitro hepatitis C virus (HCV) by blocking HCV entry and replication. In this report, we expand the list of viruses that are inhibited by ARB and demonstrate that ARB suppresses in vitro infection of mammalian cells with Ebola virus (EBOV), Tacaribe arenavirus, and human herpesvirus 8 (HHV-8). We also confirm suppression of hepatitis B virus and poliovirus by ARB. ARB inhibited EBOV Zaire Kikwit infection when added before or at the same time as virus infection and was less effective when added 24 h after EBOV infection. Experiments with recombinant vesicular stomatitis virus (VSV) expressing the EBOV Zaire glycoprotein showed that infection was inhibited by ARB at early stages, most likely at the level of viral entry into host cells. ARB inhibited HHV-8 replication to a similar degree as cidofovir. Our data broaden the spectrum of antiviral efficacy of ARB to include globally prevalent viruses that cause significant morbidity and mortality. IMPORTANCE There are many globally prevalent viruses for which there are no licensed vaccines or antiviral medicines. Some of these viruses, such as Ebola virus or members of the arenavirus family, rapidly cause severe hemorrhagic diseases that can be fatal. Other viruses, such as hepatitis B virus or human herpesvirus 8 (HHV-8), establish persistent infections that cause chronic illnesses, including cancer. Thus, finding an affordable, effective, and safe drug that blocks many viruses remains an unmet medical need. The antiviral drug arbidol (ARB), already in clinical use in several countries as an anti-influenza treatment, has been previously shown to suppress the growth of many viruses. In this report, we expand the list of viruses that are blocked by ARB in a laboratory setting to include Ebola virus, Tacaribe arenavirus, and HHV-8, and we propose ARB as a broad-spectrum antiviral drug that may be useful against hemorrhagic viruses.